Mure-multimodal regional: reestructuración de la infraestructura ambiental y recuperación de las cuencas hídricas para la región Sumapaz y Soacha (2019)
The document presents the description of an urban - architectural project in its complete development. From a specific urban site with particular conditions, under the needs of the nearby population or under study. The problem action is presented from academic and professional points as a real exercise. That can contribute to the knowledge and development of the City.